Huangqin Qingre Chubi Capsule inhibits rheumatoid arthritis by regulating intestinal flora and improving intestinal barrier - Peng, Yanhui; Huang, Yurong; Li, Hui; Li, Chen; Wu, Yajie; Chen, Zhe-Sheng; Wang, Xiao; Liao, Faxue; Miao, Chenggui (Frontiers in Pharmacology, 2024)
Abstract Background: Changes in intestinal flora and intestinal barrier in patients with preclinical and diagnosed rheumatoid arthritis (RA) suggest that intestinal flora and intestinal barrier play an important role in the induction and persistence of RA. Huangqin Qingre Chubi Capsule (HQC) is a clinically effective herbal formula for the treatment of RA, but its therapeutic mechanism has not been fully clarified. Materials and methods: In this study, real-time qPCR (RT-qPCR), 16SrRNA sequencing, Western blot (WB), immunofluorescence and other methods were used to investigate whether HQC inhibited RA. Results: Based on research in collages-induced arthritis (CIA) model in mice, human colon cancer cell line (Caco-2), and fibroblast-like synoviocytes (FLS) from RA patients, we found that intestinal flora was disturbed in CIA model group, intestinal barrier was damaged, and lipolyaccharide (LPS) level was increased, and HQC could regulate intestinal flora and intestinal barrier and reduce LPS translocation into blood. Antibiotic depletion weakened the anti-RA effect of HQC, and HQC fecal microbiota transplantation alleviated RA pathology. In addition, LPS increased the expression of RA pathologic factors MMP3, Fibronectin and inflammatory factors IL-6, TNF-α, IL-1β and IL-8, indicating that elevated peripheral blood level of LPS was related to RA pathology. Conclusions: The dysregulation of intestinal flora and the disruption of intestinal barrier are significant factors in the development of RA. HQC improves RA by regulating intestinal flora, intestinal barrier and inhibiting LPS translocation into blood. The study unveiles RA's new pathogenesis and laid a scientific groundwork for advancing HQC therapy for RA.